Athlete Engagement: A Qualitative Investigation of the Filipino Athlete - Valbuena, Michele Joan D.; Saunders, John; Rice, Vanessa; Aumond, Elizabeth (Silliman Journal, 2022)
Aimed at exploring the concept of athlete engagement, qualitative interviews on athlete engagement were conducted among 10 Filipino athletes who were competing at the international level. Data indicated that similar to New Zealand (Lonsdale, Hodge & Raedeke, 2007) and Canadian athletes (Lonsdale, Hodge & Jackson, 2007), Filipino athletes experienced confidence, dedication, vigour and enthusiasm as dimensions of their engagement. Filipino athletes experienced spirituality as an added dimension to their experience of engagement. Sporting experiences like relationship with coach, social support and assurance of fair play have been found to be antecedents of engagement. Love of the game and discipline were shown to be aspects of enthusiasm and dedication respectively. Flow was experienced by these athletes as a consequence of athlete engagement.